Gingival Curettage Treatment in a Case of Chronic Periodontitis: A Case Report - Dani Fajar Arifin; Ariyani Faizah; Qitarah Safa Haqiqah (Jurnal EduHealth, 2026)
Chronic periodontitis is an inflammatory disease that leads to the progressive destruction of the supporting tissues of the teeth, resulting in clinical signs such as gingival redness, bleeding, and periodontal pocket formation. One of the treatment approaches commonly used to manage this condition is gingival curettage, a procedure aimed at removing inflamed and necrotic tissue from the gingival wall to promote healing and restore periodontal health. This case report describes the management of chronic periodontitis in a 21-year-old patient who presented with a complaint of persistent gingival redness in the upper right anterior region for approximately three months. Clinical examination revealed erythematous gingiva surrounding teeth 12 and 13, accompanied by a positive Bleeding on Probing response, indicating active inflammation. Based on these findings, a diagnosis of chronic periodontitis was established, and gingival curettage was performed as part of the periodontal therapy. Following the procedure, the patient showed significant clinical improvement, characterized by the disappearance of gingival redness, the absence of bleeding on probing, and the resolution of gingival swelling. These outcomes suggest that gingival curettage can effectively reduce inflammation and improve periodontal tissue condition when appropriately indicated. Nevertheless, the success of this procedure is closely related to patient compliance with oral hygiene practices and regular dental follow-up. Further studies with longer observation periods are needed to evaluate the long-term effectiveness and stability of periodontal outcomes following gingival curettage.